Re-examination of EU normative power in light of the revised enlargement methodology towards the Western Balkans - Ana Bojinović Fenko; Faris Kočan (Međunarodni Problemi)
The aim of this article is to re-examine the concept of “EU normative power” in the revised EU approach to enlargement policy announced in 2020. Drawing on conceptualisation of power in Foreign Policy Analysis the article applies the reading of the EU’s soft and hard power – both as capability and as influence – to EU normative power. The empirical part thus identifies above four elements within the EU’s promotion of its particular norms and within the EU’s strife for international normality via enlargement policy. The results show that the new enlargement methodology does offer change of EU normative power. The EU could more effectively condition the respect of its particular norms by an exemplary domestic practice assuring its own domestic and foreign policy legitimacy and in turn by developing and applying the needed capabilities for achieving attractiveness. Even though a plan of positive conditionality and better-defined conditions in direct negotiations carries such potential, a risk exists that the biggest novelty – the ‘phasing-in’ paradigm – would only explore EU’s norm-related hard market power capabilities by keeping the Western Balkans countries as candidates forever, thus undermining EU’s legitimacy and hard power influence of negative conditionality. To promote international normality, however, the EU needs to activate other elements of soft power influence, namely agenda setting and persuasion.